2018
DOI: 10.1177/1741143218781066
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence can make a difference: The impact of principals’ emotional intelligence on teaching strategy mediated by instructional leadership

Abstract: This paper reports on a study that examined the effect of school principals’ emotional intelligence, and their instructional leadership, on improving teachers’ instructional strategies. A sample of 534 primary teachers from 54 primary schools in China was approached and invited to respond to a questionnaire. Structural equation modelling identified the relationships between three constructs – Wong’s Emotional Intelligence Scale, the Principal Instructional Management Rating Scale, and the Instructional Strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 65 publications
(102 reference statements)
0
42
0
5
Order By: Relevance
“…Some research has investigated the impact of teacher emotions on professional learning, wellbeing, and effectiveness (Chen et al 2020a, b;Taxer et al 2019). Similar research on principal emotions is ongoing (e.g., Chen and Guo 2020;James et al 2019). A meta-analysis project (Yang et al 2019) covering 116 studies in mainland China revealed a high likelihood of Chinese teachers experiencing some negative emotions such as anxiety and frustration.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has investigated the impact of teacher emotions on professional learning, wellbeing, and effectiveness (Chen et al 2020a, b;Taxer et al 2019). Similar research on principal emotions is ongoing (e.g., Chen and Guo 2020;James et al 2019). A meta-analysis project (Yang et al 2019) covering 116 studies in mainland China revealed a high likelihood of Chinese teachers experiencing some negative emotions such as anxiety and frustration.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with Shaked and Benoliel's (2019) assertion, which laid heavy emphasis on the instructional leader's role as the promoter of the teachers' classroom instruction towards an improvement of students' learning, which extended Steinbacher-Reed and Rotella's (2017) 'professional sandbox' approach to enhance school head-teacher collaboration for better learning outcomes. Further, Chen and Guo's (2018) finding from a study in China confirmed the instructional leader's influence on teachers' pedagogical strategies, in concert with emotional intelligence, and henceforth to student achievement. Data from Alam and Ahmad's (2017) work in Pakistan was suggestive of a connective tissue between instructional leadership and primary school students' achievement, with teacher commitment as mediator.…”
Section: The Link Between Instructional Leadership and Student Achievmentioning
confidence: 72%
“…El reconocimiento de la importancia de la inteligencia emocional en la construcción personal, conlleva su puesta en valor dentro del proceso de enseñanza y aprendizaje ya desde edades muy tempranas (Bueno i Torrens, 2017; Sepúlveda, Mayorga-Fernández y Lacal, 2019). En este contexto, surge la necesidad de reflexionar sobre cómo introducirlo en la escuela: el valor pedagógico de considerar la inteligencia emocional y la educación emocional (Del Carmen y Portillo-Peñuelas, 2018; Sadipour, Ghavam, Farrokhi, Assadzadeh y Sameti, 2019), el uso de metodologías, de recursos y materiales didácticos (Chen y Guo, 2018), qué cómo y para qué evaluar (Rodrigo-Ruiz, Cejudo y Pérez, 2019), qué agentes deben participar, factores que intervienen en el desarrollo de la inteligencia emocional (Alonso Ferres, Berrocal de Luna y Jiménez Sánchez, 2018; Alam y Ahmad, 2018; Pulido-Acosta y Herrera-Clavero, 2019; Hu, Shang y Xia, 2019).…”
Section: La Educación Emocional En Educación Primariaunclassified